Effect of Court-Type Thai Traditional Massage Versus Senokot Treatment on Chronic Constipation: A Randomized Controlled Trial - Jurairat Boonruab PhD; Phiyaphon Poonsuk MSc; Watchara Damjuti PhD (SAGE Publishing, 2020)
Chronic constipation is the disturbances of intestinal motility which is a challenge in primary healthcare around the world. In this study, Court-type Thai traditional massage and Senokot, treatments were assessed and compared in terms of their efficacy in relieving constipation. Forty subjects diagnosed with constipation were recruited and randomized into the massage group and drug group. For 7 days, Thai traditional abdominal massage was provided regularly for the patients in the massage group, while the drug group was subjected to Senokot treatment only. The Bristol stool chart scale and demographics questionnaire were used as instruments. As a result, both court type Thai traditional massage and Senokot are effective in relieving constipation. However, although both treatment options can increase the frequency of defecations and the sensation of complete evacuation, the court type Thai traditional massage seems to be better since it leads to normal defecations rather than watery or entirely liquid defecations with no solid pieces ( p < 0.05). This randomized controlled trial suggested that Thai traditional abdominal massage can be used as an optional public health treatment for constipation.